The nature and function of setting in Jane Austen's novels - Kelly, Patricia Marguerite Wyndham (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1979)
This study examines the settings in Jane Austen's six novels. Chapter I introduces the topic generally, and refers briefly to Jane Austen's aims and methods of creating her settings. Short accounts are given of the emphasis put on setting in the criticism of Jane Austen's work; of the chronology of the novels; and of the use made of this aspect of the novel in eighteenth-century predecessors. Chapter II deals with the treatment of place in Northanger Abbey, Sense and Sensibility, Pride and Prejudice, Mansfield Park and Emma. The consideration of five novels together makes it possible to generalize about aspects of place common to all , and to discuss particulars peculiar to individual novels without, I hope, excessive repetition. The chapter may be thought disproportionately long, but this aspect of setting is most prominent and important in the delineation of character. Chapter III discusses the handling of spatial detail and time in these five novels. Chapter IV offers a fuller analysis of what is the chief concern of this thesis, the nature and function of setting, in respect of the single novel Persuasion, and attempts to draw together into a coherent whole some of the points made in Chapters II and III. Persuasion separates conveniently from the other works, not only because it was written after them, but more importantly because in it there is a new development in Jane Austen's use of setting. Some critics, notably E.M. Forster and B.C. Southam, have found startlingly new qualities in the setting of Sanditon, and, certainly, the most striking feature of the fragment is the treatment of place. But Jane Austen left off writing Sanditon in March 1817 because of illness, and the twelve chapters make up too small and unfinished a piece to be considered in the same way as the other novels. The Watsons, too, except for some references to it in Chapter I, does not come within the scope of this dissertation. Another introductory point needs to be made briefly. Where it is necessary, the distinction between Jane Austen and the omniscient narrator is observed, but generally, partly because it is clear that Jane Austen's values are close to those of the narrator, and partly because it is convenient, traditional and sensible to do so, the name "Jane Austen" is used to refer both to the actual person and to the narrator of the novels.
Keywords: Austen, Jane, 1775-1817; English fiction -- Eighteenth century; Austen, Jane, 1775-1817 -- Setting; Austen, Jane, 1775-1817. Northanger Abbey; Austen, Jane, 1775-1817. Pride and Prejudice; Austen, Jane, 1775-1817. Mansfield Park; Austen, Jane, 1775-1817. Emma